PENGEMBANGAN MEDIA PEMBELAJARAN QUIZIZZ UNTUK MENINGKATKAN MINAT BELAJAR SISWA MATERI SIFAT – SIFAT CAHAYA IPA KELAS V SDN KUTAMANEUH I - Iis Karmilah; Misbah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop and implement Quizizz-based learning media to increase the learning interest of 5th grade students of SD Kutamaneuh 1 on the material of light and its properties. Through a quantitative approach with a pre-experiment research design, this study involved students as research subjects. Data collection was carried out through a learning interest questionnaire before and after treatment and observation of student activity during learning. The results showed an increase in student interest in learning after the application of Quizizz learning media. This is indicated by an increase in the average score of students' interest in learning in the post- test compared to the pre-test. In addition, observations also showed an increase in student activity and participation during the learning process. Thus, it can be concluded that Quizizz learning media is effective in increasing students' interest in learning about light and its properties. This research is expected to contribute to the development of innovative learning media and attract students' interest in learning